Early diagenetic processes associated with preservation of organic matter in concretions from the Toarcian oceanic anoxic event (Germany) and modern microbialites (Australia): A combined organic and inorganic geochemical approach - Plet, Chloé Lise (Curtin University, 2016)
A combination of inorganic and organic techniques, and powerful imaging tools was used to investigate different types of induced biomineralisations. The interest of cross-disciplinary investigation helps to develop a better understanding of induced biomineralisations and the potential they hold for early life studies. The techniques were applied to concretions from ancient times that were formed within the sediment during the Toarcian anoxic event (Germany) and to modern microbial mats from a hypersaline tidal environment (Australia).